POLITIK LUAR NEGERI INDONESIA ERA COVID-19: PENYELAMATAN DAN KERJASAMA - Asep Setiawan (Independen, 2020)
This article aims to examine Indonesia's foreign policy in the era of the Covid-19 pandemic. Based on the character of Indonesia's foreign policy which places the protection of Indonesian citizens (WNI), there are two foreign policies that stand out. First, Indonesia has prioritized rescuing Indonesian citizens abroad in places affected by the Covid-19 pandemic by means of massive repatriation. Second, still in the character of saving Indonesian citizens, Indonesia has established bilateral cooperation with China and other foreign private parties in the search for an Covid-19 vaccine. This vaccine is expected to be able to save citizens who are both inside and outside Indonesia by 2021. These two phenomena have characterized the implementation of foreign policy under Joko Widodo administration during Covid-19.